Decentralised DC voltage control and flexible power regulation for multi‐port converter‐based energy router. Issue 18 (18th June 2019) - Huang, Xin; Wang, Keyou; Qi, Chen; Li, Guojie; Zhu, Zheng
Abstract : The idea of 'energy router' (ER) is put forward as a critical application of the energy Internet (EI), especially in the new generation of electric power system to fulfil the power management and to deal with the integration of massive distributed generations. Furthermore, AC/DC hybrid network becomes a kind of development trend since it can improve the power quality and efficiency compared with adding converters for DC loads. This article proposes a decentralised control method for multi‐port converter (MPC)‐based ERs to achieve flexible power regulation and 'plug and play' operation. With the proposed schemes, DC bus voltage can be maintained together by multi‐ER through appropriately adjusting their transmitted power according to the pre‐set power‐sharing ratio. Furthermore, the sharing ratio can be online changed for flexible power regulation. The stability of the system is ensured by Lyapunov method, detailed simulation results are presented to validate the feasibility of the proposed scheme under different operating conditions.